2021
DOI: 10.1667/rade-20-00272.1
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recovery of Small Intestinal Segments after Partial-Body Irradiation in Non-Human Primates

Abstract: In the event of a radiological attack or accident, it is more likely that the absorbed radiation dose will be heterogeneous, rather than uniformly distributed throughout the body. This type of uneven dose distribution is known as partial-body irradiation (PBI). Partial exposure of the vital organs, specifically the highly radiosensitive intestines, may cause death, if the injury is significant and the post-exposure recovery is considerably compromised. Here we investigated the recovery rate and extent of recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…TBI with a certain portion of BM shielding (5 to 50%) has been shown to compromise the functional integrity of the intestine in NHPs [ 30 , 32 , 35 , 39 , 74 ]. Recently, we reported that PBI doses of 8, 11, and 14 Gy with 50% BM spared induced a dose-dependent increase in intestinal injury characterized by reduced villous height, crypt depth, and mucosal surface area by day 10 [ 75 ]. Studies have shown that 11 Gy PBI with 5% BM shielding in an NHP model induce maximum structural injury to the intestine by day 9 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBI with a certain portion of BM shielding (5 to 50%) has been shown to compromise the functional integrity of the intestine in NHPs [ 30 , 32 , 35 , 39 , 74 ]. Recently, we reported that PBI doses of 8, 11, and 14 Gy with 50% BM spared induced a dose-dependent increase in intestinal injury characterized by reduced villous height, crypt depth, and mucosal surface area by day 10 [ 75 ]. Studies have shown that 11 Gy PBI with 5% BM shielding in an NHP model induce maximum structural injury to the intestine by day 9 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two critical determinants of the extent of jejunal damage are apoptotic cell death and loss of crypt cell proliferation [ 77 ]. Importantly, we have shown jejunum as one of the most radiosensitive regions of the small intestine [ 75 ]. Interestingly, in this study, GT3 significantly enhanced crypt survival at day 4 post-PBI; however, the effect was lost by day 7.…”
Section: Discussionmentioning
confidence: 99%